Analisis Performansi Algoritma LEACH-C pada Wireless Sensor Network - Aini, Latifah Zain Nur; Ikhwan, Syariful; Amri Ginting, Jafaruddin Gusti (Arcitech: Journal of Computer Science and Artificial Intelligence, 2023)
Wireless Sensor Network (WSN) is a wireless network infrastructure that requires sensor nodes to process information and communicate. Small sensor nodes generally use batteries as their energy source, causing sensor nodes to have limited power, therefore energy efficiency is needed to extend network life. The solution to overcome these problems is by using the clustering method. In this study the cluster-based routing algorithm used is LEACH-C which can function to allocate overall energy consumption between sensor nodes. In this study, LEACH-C divides the network into several clusters, each of which has a cluster head (CH). cluster head is performed at the base station based on the average energy size of all nodes. The research simulation uses a scenario of changing nodes 50, 100, and 150. The simulation results show that the number of nodes affects the value of energy consumption, the number of data packets received, and the number of packet losses.